Upaya Meningkatkan Perkembangan Agama dan Moral Anak Usia Dini Melalaui Tayangan Animasi Islami di PAUD Kuntum Melati Sunggal - Khadijah, Khadijah; Nofianti, R.; Parapat, A. (Early Childhood Research and Practice, 2026)
The purpose of this study was to analyze and assess the extent to which Islamic animation programs can improve the religious and moral development of early childhood at Kuntum Melati Sunggal Preschool. The method used was classroom action research in two cycles, each cycle consisting of Planning Preparation, Planning, Acting, Observation, Interviews, Action, and Reflection. Each cycle consisted of two meetings. The research subjects consisted of 15 children. The results obtained in the pre-cycle research were 22%, with an increase in children's ability to apply the etiquette of asking permission, please, and thank you in cycle I by 41%. After improvements were made in cycle II, there was a significant increase in children's abilities of 80%. Therefore, it can be concluded that this research is successful.